Theoretical considerations of hydrogel therapy for periodontal tissue regeneration - Falcon-Guerrero, Britto Ebert (2024)
The removal of alveolar bone and periodontal ligament due to periodontal disease oftenrequires a surgical approach to reshape the biological structure and functions of theperiodontium. Hydrogel, a functional polymeric material, has emerged as a promising technology for periodontal disease therapies. It has the versatility to mimic the extracellular matrix and provide suitable binding sites and growth environments for periodontal cells, with high biocompatibility, water retention, and slow release. A review of the past 5 years of literature has been conducted, summarizing the main components of hydrogel in periodontal tissue regeneration.